Xplus: A SQL-Tuning-Aware Query Optimizer - Herodotou, Herodotos; Babu, Shivnath (My University, 2010)
The need to improve a suboptimal execution plan picked by the query optimizer for a repeatedly run SQL query arises routinely. Complex expressions, skewed or correlated data, and changing conditions can cause the optimizer to make mistakes. For example, the optimizer may pick a poor join order, overlook an important index, use a nested-loop join when a hash join would have done better, or cause an expensive, but avoidable, sort to happen. SQL tuning is also needed while tuning multi-tier services to meet service-level objectives. The difficulty of SQL tuning can be lessened considerably if users and higher-level tuning tools can tell the optimizer: "I am not satisfied with the performance of the plan p being used for the query Q that runs repeatedly. Can you generate a (δ%) better plan?" This paper designs, implements, and evaluates Xplus which, to our knowledge, is the first query optimizer to provide this feature. Xplus goes beyond the traditional plan-first-execute-next approach: Xplus runs some (sub)plans proactively, collects monitoring data from the runs, and iterates. A nontrivial challenge is in choosing a small set of plans to run. Xplus guides this process efficiently using an extensible architecture comprising SQL-tuning experts with different goals, and a policy to arbitrate among the experts. We show the effectiveness of Xplus on real-life tuning scenarios created using TPC-H queries on a PostgreSQL database.
Keywords: SQL; Xplus